PEMAKAIAN KONTRASEPSI SAAT INI DAN KEINGINAN DI MASA MENDATANG (Analisis SDKI 2007) - , BUDYAWATI, S.SOS, Dr. Erwan Agus Purwanto, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Contraceptive use is an effort to control birth rate in Indonesia. In order to reach the goal, family planning service must be high quality, which are signed by high rate in contraceptive use and rational to choose a contraceptive method in according with the womenâs purpose of pregnancy control. The other important thing is comprehensive information about contraceptive use that is provided by family planning clinics or family planning field workers. It is needed to improve contraceptive use to be effectively and avoidable from drop out. The objectives of this research are to know the differences on contraceptive use by age, number of living children, fertility preference, number and children sex, highest educational level, women occupation, and family planning counceling. The others objectives are to know intention of future contraceptive use, method intend to use in the future and the main reasons not intend to use contraception in the future. This study uses Indonesian demographic and health survey data conducted in 2007, with 33 provinces as research location. The subject of this research is currently married women between 15-49 years old. Data were analyzed using univariable analysis and bivariable analysis with chi square test. The result of the analyses show that there are significant differences on contraceptive use by age, number of living children, fertility preference, number and children sex, highest educational level, women occupation, and family planning counceling. The highest contraceptive use is among women with age group between 25-34 years old, having two living children, do not want any more children, having 0-2 sons and more than 2 daughters, middle educational level, professional worker and got family planning counceling. Women who are currently not using any contraceptive method, about a half of them intend to use contraception in the future and most of them desire to use injection and pill that are include of short term contraception. Meanwhile, the greatest reasons of women who are currently not using any contraceptive method and also do not intend to use contraception in the future are because of fertility (menopausal, infecund and want more children) and contraception methods such as fear of side effects and health problems. Short term contraception is preferably to use than long term contraception by women both current and future method choice. Meanwhile, the reasons do not want to use contraception in the future that are need an intervention from the government to be solved, are because of want more children, fear of side effects and health problems. Therefore, family planning counceling is needed to decrease those problems. Expanding and improving family planning services would help respond to the womenâs need of contraceptive use and would be a good public policy in the controlling birth rate in Indonesia.